Innovative model of collaboration between schools and parents to encourage healthy lifestyles among elementary school students through the friday smart program - Karisma Kamila; Innany Mukhlishina (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze the collaboration between schools and parents in promoting healthy lifestyles through the Smart Friday Program at SD Muhammadiyah 08 Dau. This study uses a descriptive qualitative research method with the principal, teachers, students, and parents as research subjects. Data were collected using observation, interviews, and data triangulation. The data were then analyzed using thematic analysis, which included data reduction, data analysis, and conclusion analysis. Data validity was achieved through source and technique triangulation. The findings showed that the Smart Friday Program, which consisted of activities such as cheerful gymnastics, guest studies, balanced nutrition, and Clean Friday, had a positive effect on students' healthy lifestyle choices at school and at home. Collaboration between schools and individuals can increase students' consistency in adopting healthy lifestyles. However, the scope of this study was limited to one school and did not use quantitative analysis to measure the program's impact statistically significantly. Therefore, further research with more comprehensive subjects and methodologies is recommended to improve the research